Indeks Partisipasi Keluarga Peternak dalam Usaha Peternakan Domba Garut di Kecamatan Targong Kaler, Kabupaten Garut - Firman, Achmad; Nurlina, Lilis; Ramdani, Diki; Rismayanti, Yayan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Garut sheep is a livestock commodity that has been designated as an indigenous breed of Garut Regency. This livestock has become part of most of the agricultural communities of Garut Regency. This research was conducted in August - September 2024 and was conducted in Tarogong Kaler District. The number of respondents who became the sample was 61 farmers. The analysis method used is the participation rate which is determined by the number of activities inside the farm and outside the farm. The participation index is the ratio between on-farm and off-farm activities compared to the standard eight-hour workday. Based on the description of the research results, it shows that the participation of fathers, mothers, and children in the Garut family sheep farming business is dominated by the father as the person in charge of the family. Mothers and children have not contributed significantly in helping in the family farm. This condition affects the participation index value of each family member, where the father has a high participation index value compared to the child and mother.